Upaya Penurunan Waktu Proses Changeover pada Mesin Novax AD di PT. X - Edo Kurniawan; I Nyoman Sutapa (Jurnal Titra, 2021)
PT. X is a company engaged in the production of cosmetic packaging. The problem faced by the company is the changeover time of the Novax AD Machine which exceeds the company’s target. The company has made improvements to the engine changeover activity. The changeover time after implementation of the improvement still exceeds the target set by the company. The purpose of this research is to provide a changeover design to reduce the changeover time. The methods used are Single Minute Exchange of Dies (SMED) and Define Measure Analyze Improve Control (DMAIC). Activities carried out for repairs are preparation activities, color actions, blower settings, and printing area positioning. Improvement efforts made by the author are the use of a colorimeter, torque wrench, the use of a special box for setup equipment, and the application of a maintenance blower. Control of proposed improvements is by making tool use guidelines and a checklist for the blower maintenance schedule. Implementation cannot be done because there is no setup schedule. The making of proposal has been discussed with the head of production who understands the machine setup in detail. The proposal is believed to reduce the changeover time because it has answered the root cause of each setup activity.